Conflicts, identity crisis and the withering away of the African Union: a quest for a new (O) AU - Mudasiru, Surajudeen Oladosu (2014)
This paper examines the issue of conflict and identity crisis and its implications for the continuous existence of the African Union. It explains the failure of the African Union to forge unity among its members in different regions of the continent in order to forge a formidable international organization it was meant to be. The paper outlines the various possibilities available to African Union which can guarantee a virile and formidable international organization that is capable of promoting stable polity and economy within the continent and how this has not yielded any positive fruits for the African Union. The paper examines the overlapping memberships of the various regional economic commissions within the continent as veritable tools for promoting peace and stability within member states and the failure of the African Union as an organization to catch in on this, particularly with the neglect of the countries of the North and the subsequent crises that erupted therein. The paper concludes by explaining the need for the African Union to refocus and establish strong ties among the RECs or withers away and pave way for a new African Union